THE PLACE OF DEVELOPMENTAL EDUCATION IN IMPROVING THE PROFESSIONAL COMPETENCE OF PRIMARY CLASS TEACHERS IN THE SYSTEM OF PROFESSIONAL IMPROVEMENT - Nargiza Karimova Rakhimova (International Journal of Innovations in Engineering Research and Technology, 2023)
The role of education in the life of society is increasing day by day. It is known that education is the main and most effective means of preparing the young generation for life. At the same time, it is also a means of rationally reducing human experience in the field of production, technology, and management.